Pendampingan Laporan Keuangan Sebagai Penunjang Dalam Penjualan Pada UMKM Wong Djamoe - Khairunnisa Rosyadah; Nabella Rosa Anggun Pitaloka; Oktavia Shintianingrum; Azki Nur Halimah; Yudha Adriansa; Mu’tasim Billah (Jurnal Pengabdian Masyarakat Nusantara, 2023)
MSMEs (Micro, Small, and Medium Enterprises) are the most important contributors to the national economy. However, in practice, many MSMEs need to optimize their capabilities because they need further information on implementing accounting in their companies. Therefore, this article aims to study the extent to which Micro, Small, and Medium Enterprises (MSMEs) apply reporting and accounting reporting as a tool for analyzing business performance. The implementation method uses the FGD (Focus Group Discussion) method with MSME actors Wong Djamoe. The results of this study indicate that the obstacle in MSMEs Wong Djamoe is the difficulty distinguishing between own capital and venture capital.